2017
DOI: 10.1039/c7ay00597k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of six derivatizing agents for the determination of nine synthetic cathinones using gas chromatography-mass spectrometry

Abstract: Six acylation reagents have been compared for their derivatisation potential towards nine synthetic cathinones by gas chromatography-mass spectrometry (GC-MS). The evaluated reagents were pentafluoropropionic anhydride (PFPA), trifluoroacetic anhydride (TFA), chlorodifluoroacetic anhydride (CLF 2 AA), heptafluorobutyric anhydride (HFBA), acetic anhydride (AA) and propionic anhydride (PA). The synthetic cathinones included flephedrone (4-fluoromethcathinone or 4-FMC), mephedrone (4-methylmethcathinone or 4-MMC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…N-Ethylnorpentylone is a synthetic cathinone that is being encountered in recreational drug markets worldwide, yet little is known about its toxicology or pharmacology. 26,27 Numerous analytical methods are published describing analyses of synthetic cathinones in biological samples, [31][32][33][34][35][36][37] but only two articles have reported quantitation of N-ethylnorpentylone. 26,27 Here we present a fully validated method to detect and quantify this substance in whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…N-Ethylnorpentylone is a synthetic cathinone that is being encountered in recreational drug markets worldwide, yet little is known about its toxicology or pharmacology. 26,27 Numerous analytical methods are published describing analyses of synthetic cathinones in biological samples, [31][32][33][34][35][36][37] but only two articles have reported quantitation of N-ethylnorpentylone. 26,27 Here we present a fully validated method to detect and quantify this substance in whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of ATSs and cathinones by GC generally requires the use of derivatizing reagents. Based on literature data [25], PFPA, which is recognized as the best acylation reagent for ATSs and cathinones, was used in our study. However, the authors of the above article investigated only a few cathinones; therefore, the derivatization temperature and time were optimized in our study (data not shown).…”
Section: Extraction and Derivatizationmentioning
confidence: 99%
“…In our developed method, the volume of solvent used (1 mL) was similar to that required for LC-MS/MS-based methods. There are limited data available concerning multi-component methods for the analysis of cathinone derivatives using GC-MS, and most of the available literature is limited to case reports of intoxications [34] or the optimization of derivatization processes [25]. To the best of our knowledge, based on previous reports, the maximum number of ATSs and NPS that can be quantified by GC-MS in a single analytical run was 26 [3].…”
Section: Comparison With Other Analytical Proceduresmentioning
confidence: 99%
“…Generally, derivatization can significantly enhance mass spectral sensitivity and alter fragmentation patterns by reducing the polarity and affecting the volatility . Acylation techniques, such as trifluoroacetylation (TFA derivatization), which is one of the most important derivatization techniques in forensic drug analysis, have been widely exploited for phenylethylamine‐type drugs, including synthetic cathinones . Full scan mass spectra of the TFA derivatives of the three FMC positional isomers exhibited the fragment ions at m / z 56, 69, 95, 110, 123, and 154 (base peak), in which characteristic fragment ions, which enable differentiation of the isomers, were not found (Figure B).…”
Section: Resultsmentioning
confidence: 99%